Serum alpha-fetoprotein levels in acute viral hepatitis. Issue 12 (December 1973) - Kew, M. C.; Purves, L. R.; Bersohn, I.
Abstract : Serum alpha-fetoprotein levels were measured serially by radioimmunoassay in 32 patients with acute viral hepatitis. With one exception, the levels were increased during the course of the illness. Raised concentrations of the protein occurred almost equally in patients with and without the hepatitis-B antigen. In the majority of patients the rise was modest but in seven levels were reached at which alpha-fetoprotein could be detected by immunodiffusion. Very high levels were more likely to occur in children. In eight patients the concentration increased as the serum glutamic pyruvic transaminase (SGPT) level, used as an index of hepatocyte damage, was returning to normal, a pattern which favoured increased synthesis of the protein during hepatocellular regeneration. In the remainder, the alpha-fetoprotein level paralleled that of SGPT, suggesting rather an acutephase reaction to liver injury.